Insights into cetacean sightings, abundance, and feeding associations: observations from the boat lift net fishery in the Kaimana important marine mammal area, Indonesia - Putra, Mochamad Iqbal Herwata; Malaiholo, Yance; Sahri, Achmad; Setyawan, Edy; Herandarudewi, Sekar M. C.; Hasan, Abdy W.; Prasetio, Hanggar; Hidayat, Nur Ismu; Erdmann, Mark V. (Frontiers in Marine Science, 2025)
A comprehensive understanding of cetacean ecology is crucial for conservation and management. In 2018, Kaimana was identified as an Important Marine Mammal Area (IMMA) due to the regular presence of feeding aggregations of Australian humpback dolphins (Sousa sahulensis), Pacific bottlenose dolphins (Tursiops aduncus) and Bryde's whales (Balaenoptera edeni). Despite this, information on cetacean ecology in the Kaimana region is currently lacking. Notably, no cetacean surveys have been undertaken in Kaimana since it was officially recognized as an IMMA. We monitored food-provisioning interactions between lift-net fisheries and cetaceans from May 2021 to March 2023 to examine cetacean sightings, abundance and feeding associations. Five species were positively identified, including a new record of Killer whales (Orcinus orca). Our findings suggest a strong association between T. aduncus and lift-net fisheries, where they have been observed feeding on anchovies from outside the net in the morning. While other species were also observed, their presence was less frequent. Furthermore, year-round sightings of S. sahulensis, B. edeni, and T. aduncus during the study period indicate that these species are resident in this region. Our results suggest that Kaimana fulfills a second IMMA sub-criterion (small and resident populations of these three species) that was not previously noted in the original IMMA assessment.